2012
DOI: 10.1016/j.febslet.2012.04.018
|View full text |Cite
|
Sign up to set email alerts
|

LPS‐induced chemokine expression in both MyD88‐dependent and ‐independent manners is regulated by Cot/Tpl2‐ERK axis in macrophages

Abstract: Edited by Masayuki MiyasakaKeywords: Macrophage Chemokine LPS Cot/Tpl2 ERK a b s t r a c t LPS signaling is mediated through MyD88-dependent and -independent pathways, activating NF-jB, MAP kinases and IRF3. Cot/Tpl2 is an essential upstream kinase in LPS-mediated activation of ERKs. Here we explore the roles of MyD88 and Cot/Tpl2 in LPS-induced chemokine expression by studying myd88 À/À and cot/tpl2 À/À macrophages. Among the nine LPS-responsive chemokines examined, mRNA induction of ccl5, cxcl10, and cxcl13 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
54
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 48 publications
11
54
0
Order By: Relevance
“…Consistent with previous reports, Fos, IL-1␤, and the chemokines CCL2, CCL7, and CXCL3 were reduced in the absence of Tpl2, whereas IL-12p40 (IL-12B) and IFN␤ expression were increased (Fig. 1A) (26,(32)(33)(34). These findings served to verify the microarray results.…”
Section: Chemokine Receptor Expression Is Impaired In Tpl2supporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with previous reports, Fos, IL-1␤, and the chemokines CCL2, CCL7, and CXCL3 were reduced in the absence of Tpl2, whereas IL-12p40 (IL-12B) and IFN␤ expression were increased (Fig. 1A) (26,(32)(33)(34). These findings served to verify the microarray results.…”
Section: Chemokine Receptor Expression Is Impaired In Tpl2supporting
confidence: 92%
“…4). In this regard, Bandow et al (32) have shown previously that the LPS-induced expression of the CCR1/CCR5 specific chemokine ligand CCL5 (RANTES), was increased in tpl2 Ϫ/Ϫ macrophages. We also observed a timedependent increase in CCL5 expression levels in tpl2 Ϫ/Ϫ macrophages (data not shown).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…We examined the possible involvement of Cot/Tpl2, an essential upstream kinase for the LPS-induced ERK phosphorylation in a variety of cell types (17)(18)(19)(20)(21). We found that Cot/Tpl2 was rapidly phosphorylated in LIPUS-stimulated 3T3-L1, MC3T3-E1, and ST2 cells (Fig.…”
Section: Lipus-induced Signals Are Mediated By Cot/tpl2mentioning
confidence: 98%
“…These signalling pathways produce pro-inflammatory cytokines via p38, JNKs, ERKs, and IKK protein kinase cascades, leading to activation of transcription factors such as NF-κB AP-1 and IRF3, which promote expression of cytokine-encoding genes. Therefore, LPS-mediated production of cytokines (IL-6, TNF-α, IL-1β, MCP-1, IFN-β) in RAW264.7 cells occurs via PI3K/Akt, MAPK, JAK/STAT pathways [37-42]. …”
Section: Discussionmentioning
confidence: 99%